TECHNIKI OBRAZOWANIASinus venosus atrial septal defect diagnosed by cardiac magnetic resonance imaging. A case report - Miszalski-Jamka, Karol; Głowacki, Jan; Kalarus, Zbigniew; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
Sinus venosus atrial septal defect is an uncommon congenital heart defect, which requires appropriate diagnosis. We present a case of a 23-year-old female suspected of pulmonary hypertension. Both transthoracic echocardiography and computed tomography failed to establish the correct diagnosis. Finally, cardiac magnetic resonance demonstrated the presence of sinus venosus atrial septal defect with partial anomalous pulmonary venous drainage. The patient was referred for surgical treatment.